Attachment between heterotrophic bacteria and microalgae influences symbiotic microscale interactions - Ty J. Samo; Jeffrey A. Kimbrel; Daniel J. Nilson; Jennifer Pett‐Ridge; Peter K. Weber; Xavier Mayali (Environmental Microbiology, 2018)
Summary The surface and surroundings of microalgal cells (phycosphere) are critical interaction zones but have been difficult to functionally interrogate due to methodological limitations. We examined effects of phycosphere‐associated bacteria for two biofuel‐relevant microalgal species ( Phaeodactylum tricornutum and Nannochloropsis salina ) using stable isotope tracing and high spatial resolution mass spectrometry imaging (NanoSIMS) to quantify elemental exchanges at the single‐cell level. Each algal species responded differently to bacterial attachment. In P. tricornutum , a high percentage of cells had attached bacteria (92%–98%, up to eight bacteria per alga) and fixed 64% more carbon with attached bacteria compared to axenic cells. In contrast, N. salina cells were less commonly associated with bacteria (42%–63%), harboured fewer bacteria per alga, and fixed 10% more carbon without attached bacteria compared to axenic cells. An uncultivated bacterium related to Haliscomenobacter sp. was identified as an effective mutualist; it increased carbon fixation when attached to P. tricornutum and incorporated 71% more algal‐fixed carbon relative to other bacteria. Our results illustrate how phylogenetic identity and physical location of bacteria and algae facilitate diverse metabolic responses. Phycosphere‐mediated, mutualistic chemical exchanges between autotrophs and heterotrophs may be a fruitful means to increase microalgal productivity for applied engineering efforts.